TECHNOLOGICAL CIVILIZATION AND THE PHILOSOPHICAL FOUNDATIONS OF SOCIO-CULTURAL PROCESSES (Scientific journal of the Fergana State University, 2026)
This article analyzes the philosophical essence of the concept of sociocultural technologies, their role in the development of society, and their impact on the cultural formation of human activity. The study examines the management of sociocultural processes based on a technological approach, as well as new forms of social technologies emerging in the context of the modern communicative environment and digital transformation.